Reducing food loss with insecticide-treated storage material - Wicoff, Clara; Campbell, James; Scheff, Deanna (My University, 2017)
At the global level, approximately one-third of food produced for human consumption is lost or wasted each year. According to the Food and Agriculture Organization of the United Nations, more than 40 percent of food losses in developing countries occurs at the post-harvest and processing levels. In developing countries stored product insects can be one of the most important loss factors. Grain commodities in developing countries is typically stored in bags in homes and in warehouses. Even if the grain added to these bags is free of insects the stored bags are vulnerable to insect colonization during storage and transport. This loss to insect damage could potentially be reduced by utilizing insecticide-treated bags to store commodities. However, to be effective a rapid knockdown of the insect is needed so they don’t gain access to the grain inside the bag.